ETNOGRAFI KOMUNIKASI TRADISI MENUMBAI SIALANG DI DESA PELALAWAN KABUPATEN PELALAWAN PROVINSI RIAU - Mukhtasyar Zulfajri; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The Menumbai Sialang Ritual is one of the traditions carried out by the indigenous Pelalawan community until now. This ritual is carried out in the forests and plantations of rural communities. The tradition of menumbai sialang aims to take or harvest forest bee honey nesting in the Sialang tree. Besides this tradition also aims to establish relationships between communities. Because not only are landowners allowed to take part in the Sialang Menumbai ritual procession, but villagers are also allowed to follow this Tradition. Tassel sialang comes from the word umbai, which means down or lower by using a tool. maumbaian (lowering) in the form of ropes and baskets. This word describes the motion of lowering the honeycomb by using timbo (bucket) which is lowered with a rope. This study uses qualitative meode with a descriptive approach. The object of this research is the ethnography of the communication of the Menumbai Sialang tradition in Pelalawan Village, Pelalawan Regency, Riau Province, with the research subjects meeting the research needs of 5 people. Data collection techniques in this study used in-depth observation, interviews and documentation. The results of this study are ethnographic communication of Menumbai Sialang which are divided into three forms: communicative situations, communicative events and communicative actions. The communication situation is in the form of participant preparation and setting of the Sialang Menumbai ritual. Communicative events include topics, norms and rules of interaction and the contents of messages and actions in the form of singing or Tombai hinga mantra in the process. In communicative actions that concern the knowledge of a Jagan about Sialang Tassel culture, which is useful for interpreting the linguistic forms of Sialang Tassel ritual. Keywords: Ethnography, Communication, Menumbai Sialang, Jagan